Les mots des hommes sur des maux de femmes. Les déclarations de grossesse illégitime au bailliage de Rouen (1761-1790) - Catherine Hans Ménétrier (Genre & Histoire)
In order to prevent infanticide, punishable by death, in a 1556 order, Henry II required single mothers to declare their status. Between 1761 and 1790, these declarations were recorded in two registers at the Bailliage of Rouen. Although these documents are written in a masculine, administrative style, they also contain the rare voices of women. and provide an insight into what led these women to illegitimacy and how they approached the process of informing the authorities of their pregnancy.